ESSAI DE GERMINATION ET DE CROISSANCE AU STADE JUVÉNILE DES SOUCHES LOCALES DE JATROPHA CURCAS L. EN RÉPUBLIQUE CENTRAFRICAINE - Touckia, Gorgon Igor; Yongo, Olga Diane; Abotsi, Komla Elikplim; Wabolou, Francois; Kokou, Kouami (European Scientific Journal, ESJ, 2015)
Methods: In order tocharacterize the germination and growth of some local varieties of Jatropha curcas at nursery stage in Nzila, a village of Central African Republic, their seeds of were sown in polyethylene bags and arranged in a randomized plot design on raised beds exposed to the sun. The effects of origins and substrate on the studied growing parameters are appreciated by an analysis of variance (ANOVA), with the software R. Results.-The different substrates have significant impact on germination and growth on both devices while their origins have no significant impact. The seeds from forest areas (Nzila and Bangui) have the best rates of germination and better growth on land. They have shown more robust plants with greatest heights and diameters. In polyethylene bags, seeds from savannah areas (Bouar and Boali) are those which have the greatest heights and the largest diameters. A strong correlation was seen between studied parameters with highers values between the diameter and the number of leaves (94.31%). Conclusion In juvenile stage, plants from all origins fit well with the environmental conditions.